Skewed B cell differentiation affects lymphoid organogenesis but not T cell-mediated autoimmunity. (6th March 2014) - Colombo, E; Tentorio, P; Musio, S; Rajewsky, K; Pedotti, R; Casola, S; Farina, C
Summary: B cell receptor (BCR) signalling determines B cell differentiation and may potentially alter T cell-mediated immune responses. In this study we used two transgenic strains of BCR-deficient mice expressing Epstein–Barr virus latent membrane protein (LMP)2A in B cells, where either follicular and marginal zone differentiation (DH LMP2A mice) or B-1 cell development (VH LMP2A mice) were supported, and evaluated the effects of skewed B lymphocyte differentiation on lymphoid organogenesis and T cell responses in vivo . Compared to wild-type animals, both transgenic strains displayed alterations in the composition of lymphoid organs and in the dynamics of distinct immune cell subsets following immunization with the self-antigen PLP185–206 . However, ex-vivo  T cell proliferation to PLP185–206 peptide measured in immunized DH LMP2A and VH LMP2A mice was similar to that detected in immunized control mice. Further, clinical expression of experimental autoimmune encephalitis in both LMP2A strains was identical to that of wild-type mice. In conclusion, mice with skewed B cell differentiation driven by LMP2A expression in BCR-negative B cells do not show changes in the development of a T cell mediated disease model of autoimmunity, suggesting that compensatory mechanisms support the generation of T cell responses.